Students’ Speaking Challenges at Different English Courses in Kampung Inggris Pare Kediri - Rika Nabilah Ananda Bahari (Universitas Negeri Surabaya, 2025)
This study investigates the speaking challenges faced by students and alumni in Kampung Inggris Pare, Kediri. Employing a mixed-method approach, 92 participants from three English institutions took part in the research. Data were collected using both close- and open-ended questionnaires, then analyzed through quantitative and qualitative methods. The findings revealed that 40.3% of respondents experienced linguistic difficulties related to vocabulary, grammar, and pronunciation. Psychological issues such as low confidence (25%) and anxiety (23%) also hindered their speaking performance. Additionally, 28.5% had the opportunity to speak but did not know what to say, while 31.7% lacked interaction with native speakers. These results emphasize the need for integrated language instruction that also considers psychological and environmental factors. Future research should involve interviews or classroom observations to further explore effective strategies that support learners’ speaking confidence.